Kajian Berbagai Pola Tanam terhadap Peningkatan Produktivitas Jagung dan Kedelai dengan Berbagai Varietas Jagung - Sari, Siti Hapita; Ghulamahdi, Munif; Suwarno, Willy Bayuardi; Melati, Maya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2020)
The reduction in agricultural land due to land conversion has encouraged several technological innovations in cultivation systems, including intercropping planting patterns. The study aimed to study various intercropping patterns with several varieties of maize which can increase production. The research was conducted at the Sawah Baru Experimental Station of the IPB University, Darmaga, Bogor, from November 2018 to February 2019 using a split-plot design with three replications. The main plot was the cropping systems, consisting of monoculture, single-row intercropping, double-rows intercropping, and triple-rows intercropping. The subplot was the maize varieties, consisting of Sukmaraga, Bima 19, and BISI 2. Regression and correlation analyses were carried out to determine the relationship between microclimate and productivity. The results showed that the productivity of maize and soybean was affected by the interaction between cropping patterns and varieties. The highest productivity of maize was obtained from the intercropping pattern of double rows of BISI 2 maize (7.33 ton ha-1), while the lowest maize productivity was in the intercropping pattern of a single row of Bima 19 maize (2.93 ton ha-1). The highest productivity of soybean was obtained from the intercropping cropping pattern of a single row of BISI 2 maize. The effect of microclimate on various cropping patterns with productivity in this study was a little. Land equivalent ratios (LER) in all treatments were greater than 1 except for intercropping 1 row of Bima 19 maize, indicating that intercropping can increase land productivity. Keywords: cropping pattern, intercropping, land equivalent ratio (LER), maize varieties